PREVENTIVE FACTORS TO SERVE IN FAMILY PHYSICIAN PROGRAM (FPP): A QUALITATIVE RESEARCH - Bayati, A.; Shamsi, M.; Ghanbari, F.; Dehghan, F. (University of Eloued جامعة الوادي, 2018)
Background: One of the amendments made in Iran's Health System is family physician program (FPP) is introduced in 2004. This study aimed to describe the experiences of physicians in health team members of about serving inhibiting factors in Arak University of medical science to review the performance of this program. Methods: This study is a qualitative content analysis conducted on the members of health team. The data collection was in-depth semi-structured interviews with the participants assessing their viewpoints on preventive factors to serve in a FPP. The purposive sampling approach was used. Fifty five interviews were carried out with 15 midwives, 15 physicians, and 25 community health workers. Content analysis with conventional approaches was used to analyse the data. Results: After continuous analysis of the data two themes were extracted: management factors and public interests. These themes include five subcategories: administrative barrier factors, welfare barrier factors, motivation barrier factors, lack of orientation of the treatment and health systems, lack of orientation of the people, were created. Conclusion: The following measures are recommended: conducting training justification programs for physicians and all members of health teams and public. In addition, revising the program to remove the pitfalls of the referral system, description of workers duties and timing of the service provision are recommended.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: Family physician program (FPP), Family Health Team, Inhibiting Factors